What do African traditional medical practitioners do in the treatment of mental disorders in Zimbabwe?. Issue 1 (2nd January 2016) - Kajawu, Lazarus; Chingarande, Sunungurai D.; Jack, Helen; Ward, Catherine; Taylor, Tonya
Abstract : African traditional medicine (ATM) is an important health delivery system throughout the world, especially in sub-Saharan Africa, yet very little research has been done on it, write on it. Research suggests that ATM can be complementary to biomedicine, particularly for mental health care. In this study, we aimed to explore ATM practices on patients with mental disorders. Using exploratory qualitative methods in a semi-urban community near Harare, we conducted 30 interviews with traditional healers from Zimbabwe National Traditional Healers' Association. Data were coded and analysed using thematic analysis to identify key themes. We found that herbalists were the main healing order, and that the majority of the patients were women who presented mainly with problems identified as 'supernatural', such as witchcraft or spiritual. The ATM involved mainly using spiritual power, talking and rituals that met patients' cultural expectations. Our data suggest that ATM uses distinct treatments methods that meet cultural expectations of patients and that biomedicine do not. The ATM practices may therefore have a positive role to play in the treatment of mental disorders in Africa. Policies in national guidelines should include ATM practices to address mental health needs of the patients. More research is required to establish efficacy of ATM practices before their adoption.